UDZIAŁ KAROLA WOJTYŁY W PRACACH KONFERENCJI EPISKOPATU POLSKI I JEJ KOMISJI SPECJALISTYCZNYCH (1958–1978) - Białkowski, Michał (Studia Pastoralne, 2023)
The aim of this paper is to present the leading role of Karol Wojtyła in the works of the Episcopal Conference of Poland (ECP) in 1958–1978. Therefore, the main research problem will be a description of Karol Wojtyła’s participation and actual influence on activities of the Episcopal Conference of Poland, together with evaluation of the effects of his activities. The following hypotheses can be formulated. 1) Karol Wojtyła’s influence on works of the Episcopal Conference of Poland evolved along with his changing position in the Episcopate structures (a strong trend for the increasing influence); 2) Karol Wojtyła undertook multi-faceted, multi-directional and multidimensional actions; 3) actions undertook by Karol Wojtyła in the Episcopate of Poland significantly influenced development of relationships between the state and the Church. The studies conducted using the historical (genetic) method and content analyses allow to present the following factual data. Karol Wojtyła played an important role in works of the Episcopal Conference of Poland and its specialist committees. From 1958 (his appointment as the suffragan bishop of Krakow) he was a member of the ECP, and in 1964 (appointment as the Metropolitan Archbishop of Krakow) he joined the top management group – EP Main Committee/Main Board. As a part of the tasks he was appointed then, he prepared pastoral letters and participated in development of relationships with PRL government; he was also responsible for contacts with the Apostolic See and episcopal conferences abroad; and inspired changes in the organisational structure, aims and tasks of the Episcopal Conference of Poland. His participation in works of specialist committees represented an important part of his involvement with the Episcopal Conference of Poland. During twenty years of his service as a bishop Karol Wojtyła was a member of the following commissions: Commission for the Lay Apostolate – chairman in 1966–1978; Subcomission for Studies – chairman in 1967–1970; Commission for Catholic Education – chairman in 1970–1978; Science Council – chairman in 1972–1978; Commission for Christian Ministry – member in 1958–1978; Council Commission – member in 1963–1970; and Vocations Committee – member in 1967–1970. The number and the diversity of proposals, projects, and postulates notified by him prove the unique intellect, organisational skills and leadership skills of the future pope. skills and leadership skills of the future pope.